Meta-analysis of efficacy of topiramate in migraine prophylaxis - Guo, Yiyi; Han, Ximei; Yu, Tingmin; Yao, Gang (Neural regeneration research, 2012)
OBJECTIVE：To evaluate the treatment effects and safety of topiramate in migraine prophylaxis. DATA RETRIEVAL：We searched the Medline database,EMbase,Cochrane Library and China National Knowledge Infrastructure database for articles published between January 1995 and May 2011,using the key words＂migraine＂,＂topiramate＂,and＂prophylaxis＂. SELECTION CRITERIA：We selected randomized controlled trials of migraine patients,in which the experimental group was orally administered topiramate,and the control group was given placebo. Odds ratios（ORs）and mean differences（MDs）were calculated using a fixed effects model/random effects model.Quality evaluation and data extraction were performed independently by two researchers utilizing RevMan 5.0 software. MAIN OUTCOME MEASURES：Efficacy was recorded as the responder rate（response defined as at least a 50%reduction in average monthly migraine frequency）and change in mean monthly number of migraine days.Adverse events were recorded as the number of subjects exhibiting at least one adverse event. RESULTS：Eight randomized controlled trials were found to be appropriate,and had available data. The meta-analysis results revealed that topiramate（100 or 200 mg/d）was more effective than placebo in responder rate（OR=2.97,95%confidence interval（CI）：2.17-4.08,P〈0.01;OR=2.35, 95%CI：1.77-3.12,P〈0.01）.Topiramate（100 mg/d）was more effective than placebo in terms of the change in mean monthly migraine days（MD：-1.14,95%CI：-1.69 to-0.59,P〈0.01）.The total incidence rate of adverse events for topiramate was higher than in the placebo group（P〈0.01）,but most adverse events were mild to moderate. CONCLUSION：Overall,topiramate obtained good outcomes and safety in migraine prophylaxis.